ASSOCIATION BETWEEN CARBAMAZEPINE INDUCED SEVERE CUTANEOUS ADVERSE DRUG REACTION AND HLA POLIMORPHISMS - Ratnaningrum, Safrina Dewi (Malang Neurology Journal, 2016)
Carbamazepine as an antiepileptic drug that is used widely and was known can cause severe cutaneous adverse drug reactions like SJS-TEN. These adverse drug reactions is known to be associated with some specific HLA polymorphism in European populations (HLA-A*31: 01), China (HLA-A*31: 01; HLA-B*15: 02), Japan (HLA-A*31 : 01; HLA-B*15: 11), Korea HLA-A*31: 01; HLA-B*15: 02; HLA-B*15: 11), India (HLA-B*15: 02), Thailand (HLA-B*15: 02), and Malaysia (HLA-B*15: 02). Information related to certain HLA polymorphism is important to prevent adverse drug reaction but there is no sufficient data on the population of Indonesia.